Reducing the Hellenic Financial Crisis to Its Root Cause: A Cybernetic Analysis. (17th September 2018) - Trujillo, Joaquin
Abstract: This article cybernetically (isomorphically) investigates the causes of the Hellenic financial crisis. It (1) describes the crisis and its commonly assessed root cause: systemic corruption coupled to the decisions of ample numbers of Greeks to endure the problem rather than resolve it; (2) reviews SYRIZA's 2015 anti‐austerity campaign and identifies incompatibilities within its apparent collective purposes that imply processes more fundamental than corruption and bad faith may be causing the crisis; (3) situates cybernetics within a sociological framework to analyze those processes appropriately; (4) propositionally reduces them to a general rule—the tragedy of the commons—operating more or less within the collective conscience of the Greek people; and (5) and exposes the parameter's self‐similar manifestation in social actions that have contributed to the crisis.